2011
DOI: 10.1002/cncr.26726
|View full text |Cite
|
Sign up to set email alerts
|

A study of circulating interleukin 10 in prognostication of unresectable hepatocellular carcinoma

Abstract: BACKGROUND: The level of circulating interleukin 10 (IL‐10) is elevated in a proportion of patients with hepatocellular carcinoma (HCC). The objective of the current study was to evaluate the prognostic significance of serum the IL‐10 level in patients with unresectable HCC. METHODS: Patients with unresectable HCC who provided serum at the time of diagnosis were enrolled prospectively in the study. The level of circulating IL‐10 in serum samples was determined by enzyme‐linked immunosorbent assay. The associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 27 publications
6
41
1
1
Order By: Relevance
“…These authors concluded that HCC patients with the highest IL-8 levels had worse survival rates and recommended assessments of IL-8 during HCC. Chan et al (2012) reported that high IL-10 levels portended worse overall survival in patients with HCC. Serum IL-10 level was identified as an independent prognostic factor for unresectable HCC.…”
Section: Discussionmentioning
confidence: 99%
“…These authors concluded that HCC patients with the highest IL-8 levels had worse survival rates and recommended assessments of IL-8 during HCC. Chan et al (2012) reported that high IL-10 levels portended worse overall survival in patients with HCC. Serum IL-10 level was identified as an independent prognostic factor for unresectable HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that IL-10 is associated with viral-related inflammation in the liver [36]. Moreover, circulating IL-10 is highly up-regulated in a proportion of HCC patients, and high levels of IL-10 are related to hepatic injury caused by cirrhotic processes and predict a poor prognosis [37,38]. We found that expression of TGF-β and IL-10 increased with progression of HCC, and the relation analysis showed a positive correlation between TGF-β and IL-10 expression in HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…For the semiquantitative way, a minimum of 1000 neoplastic cells were evaluated in each mammary tumor and the VEGF-A immunoexpression was assessed according to five levels: grade 0 (no staining detected in tumor cells), grade 1 (1-24% of tumor area showed positive staining), grade 2 (25-49% of tumor stained), grade 3 (50-75% of tumor stained) and grade 4 >75% of tumor stained). The staining intensity was also evaluated as: level 0 (unstained), + (weak staining), ++ (moderate staining) and +++ (intense staining) [34]. For the quantitative way, a representative image from each tumor was taken with a 40x objective and the VEGF immunoexpression was quantified using an Image Manipulation Program 2.8 (GIMP 2.8, CNE, Free Software Foundation, Boston, USA) [35].…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%